2002
DOI: 10.1046/j.1432-1033.2002.03338.x
|View full text |Cite
|
Sign up to set email alerts
|

The C‐terminal domain of perfringolysin O is an essential cholesterol‐binding unit targeting to cholesterol‐rich microdomains

Abstract: There is much evidence to indicate that cholesterol forms lateral membrane microdomains (rafts), and to suggest their important role in cellular signaling. However, no probe has been produced to analyze cholesterol behavior, especially cholesterol movement in rafts, in real time. To obtain a potent tool for analyzing cholesterol dynamics in rafts, we prepared and characterized several truncated fragments of θ‐toxin (perfringolysin O), a cholesterol‐binding cytolysin, whose chemically modified form has been rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
141
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(146 citation statements)
references
References 33 publications
4
141
1
Order By: Relevance
“…Tryptophan residues have been implicated in hydrophobic ring and Raft interactions; FWLY 38 -41 may mediate interactions with other ring residues in LMP1 or with cholesterol-rich microdomains (53)(54)(55)(56). The failure of LMP1AALA 38 -41 to associate with Raft and Barge membrane microdomains and to signal, supports the hypothesis that LMP1 transmembrane domain-mediated intermolecular aggregation in Raft or Barge microdomains is an important nucleation event for signaling.…”
Section: Discussionmentioning
confidence: 82%
“…Tryptophan residues have been implicated in hydrophobic ring and Raft interactions; FWLY 38 -41 may mediate interactions with other ring residues in LMP1 or with cholesterol-rich microdomains (53)(54)(55)(56). The failure of LMP1AALA 38 -41 to associate with Raft and Barge membrane microdomains and to signal, supports the hypothesis that LMP1 transmembrane domain-mediated intermolecular aggregation in Raft or Barge microdomains is an important nucleation event for signaling.…”
Section: Discussionmentioning
confidence: 82%
“…It was demonstrated that at least the step of LLO binding to membrane cholesterol is affected by denaturation under neutral or alkaline pH conditions. CDCs have four functional domains, among which the C-terminal domain 4 is essential for the recognition and first binding of CDCs to target membrane (Rossjohn et al, 1997;Shimada et al, 2002). Several studies have suggested that the domain 4 of CDCs remains close to the membrane surface in the membrane-inserted oligomer without being embedded deeply in the bilayer (Heuck et al, 2000;Ramachandran et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…This was because domain 4 is responsible for the membrane-binding activity of CDCs (Shimada et al, 2002) and the leucine residue at position 461 in domain 4 is implicated in the pH-dependent cytolytic activity of LLO (Glomski et al, 2002). To confirm this possibility, we constructed domain 4 preparations of LLO and PLY as representatives of pH-sensitive and pH-insensitive CDCs, respectively.…”
Section: Membrane-and Cholesterol-binding Activity Of Domain 4 Of Llomentioning
confidence: 99%
“…Finally, as a third approach to track intracellular cholesterol content, we monitored the distribution of the cholesterolbinding domain (D4) of perfringolysin O (Shimada et al, 2002), fused to mCherry (Abe et al, 2012). When expressed in hippocampal CA1 neurons, mCherry-D4 displayed a diffuse distribution with the presence of scattered fluorescence clusters ( Fig.…”
Section: Ltp-triggered Cholesterol Redistribution Activates Cdc42 Andmentioning
confidence: 99%